Constitutional mosaic genome-wide uniparental disomy due to diploidisation: an unusual cancer-predisposing mechanism - Valeria Romanelli; Julián Nevado; Mario F. Fraga; Alejandro Martin Trujillo; M. A. Mori; Luis Carlos Sainz Fernandez; Guiomar Pérez de Nanclares; Víctor Martínez‐Glez; Guillermo Pita; H. Meneses; R Gracia; Sixto García‐Miñaúr; et al. (2010)
Molecular studies in a patient with Beckwith–Wiedemann syndrome phenotype who developed two different tumours revealed an unexpected observation of almost complete loss of heterozygosity of all chromosomes. It is shown, by means of numerous molecular methods, that the absence of maternal contribution in somatic cells is due to high-degree (∼85%) genome-wide paternal uniparental disomy (UPD). The observations indicate that the genome-wide UPD results from diploidisation, and have important implications for genetic counselling and tumour surveillance for the growing number of UPD associated imprinting disorders.